2022
DOI: 10.3390/life12081187
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Mechanisms Affecting Glucose Homeostasis: A Scoping Review

Abstract: The maintenance of a healthy status depends on the coexistence between the host organism and the microbiota. Early studies have already focused on the nutritional properties of probiotics, which may also contribute to the structural changes in the gut microbiota, thereby affecting host metabolism and homeostasis. Maintaining homeostasis in the body is therefore crucial and is reflected at all levels, including that of glucose, a simple sugar molecule that is an essential fuel for normal cellular function. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 223 publications
1
7
0
Order By: Relevance
“…In 2021, Lee et al showed in a clinical trial that treatment with Metformin led to changes in the levels of Clostridium, Escherichia, Intestinibacter, and Romboutsia [ 91 ]. These findings are consistent with the results of our study that showed the great influence Metformin has on the microbiota [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In 2021, Lee et al showed in a clinical trial that treatment with Metformin led to changes in the levels of Clostridium, Escherichia, Intestinibacter, and Romboutsia [ 91 ]. These findings are consistent with the results of our study that showed the great influence Metformin has on the microbiota [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is particularly useful as it is calculated by taking the difference between the means of these two groups and dividing it by the pooled standard deviation. As can be seen in Figure 2 , some studies [ 17 , 19 , 22 , 23 , 25 ] have a negative difference between the means of the two populations studied (calculated using Cohen’s d). This means that those who were part of the INTERVENTION group had more changes in the microbiome when compared to the CONTROL/PLACEBO group.…”
Section: Resultsmentioning
confidence: 99%
“…However, a similar attenuation effect of probiotics was observed between mice administered fructose and glucose, despite the different abundances of Lactobacilli from microbiome analysis, also indicating that the probiotic effect of our high-sugar diet model should be due to an anti-prediabetes or an anti-obesity effect. In fact, Lactobacillus , Bifidobacterium , Clostridium , and Akkermansia are indicated as a bacterial group with beneficial changes in insulin resistance through several possible mechanisms (reduced carbohydrate absorption, improved energy utilization, facilitation of some intestinal enzymes and anti-inflammation) [ 94 , 95 ]. There were a number of limitations due to the study’s “proof-of-concept” characteristics, particularly with regard to the mechanical interpretation of the observed data.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar attenuation effect of probiotics was observed between fructose-and glucose-administered mice, despite the different abundances of Lactobacilli from microbiome analysis, also indicating that the probiotic effect of our high sugar diet model should be due to an anti-prediabetes or anti-obesity effect. In fact, Lactobacillus, Bifidobacterium, Clostridium, and Akkermansia are indicated as a bacterial group with beneficial changes in insulin resistance through several possible mechanisms (reduced carbohydrate absorption, improved energy utilization, facilitation of some intestinal enzymes and anti-inflammation) [96,97]. There were a number of limitations due to the study's "proof of concept" characteristics, particularly with regard to the mechanical interpretation of the observed data.…”
Section: Lactiplantibacillus Plantarum Attenuated the Severity Of Mic...mentioning
confidence: 96%